Successful pregnancy outcome in a rare case of complete situs inversus in a primigravida - BH, Radhika; V, Harshini; Jogi, Priyanka; Ramaiah, Renuka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Complete situs inversus is a rare syndrome, of autosomal recessive inheritance, resulting from inversion of rotation of the cardiac tube during embryogenesis. It occurs in 1 in 10,000 births. We report here an interesting case where situs inversus was diagnosed during pregnancy followed by uneventful course of pregnancy. A 28 year old primigravida, presented to our hospital for first antenatal visit at 16 weeks of gestation. On physical examination she was found to have her cardiac apex on the right side in right 5th intercostal space. Presence of dextrocardia prompted a thorough physical examination, with other findings raising suspicion of total situs inversus. Confirmation of situs inversus was done by ultrasound imaging of abdomen and transthoracic echocardiography. Her obstetric ultrasonographic examination was unremarkable and showed a single alive intrauterine gestation 14 weeks gestation. She was regularly followed up & her pregnancy course was uneventful. She was admitted at term gestation, with premature rupture of membranes. An attempt to induce labour was done with four doses of oral misoprostol. Eventually she underwent emergency cesarean section due to failure of induction and an alive term female baby of weight 2.7 kg was delivered . Intra and post-operative period was uneventful. She was discharged on sixth post-operative day. Her six week postpartum follow up was uneventful. Situs inversus with pregnancy is a rare clinical entity. However, these patients are likely to have uneventful course during pregnancy.